Effects of reductive soil disinfestation on microbiological and physicochemical properties of continuous cropping soils in karst areas of Guizhou Province - Yi He; Bo Gong; Taibo Liang; Zhenbao Luo; Qiwei Yu; Caibin Li; Huawei Peng; Heqing Cai; Huaxin Dai; Zhen Zhai; Nianjie Shang; Mengjiao Ding (Annals of Microbiology)
Abstract Purpose The soil-borne diseases have limited the development of agricultural production in Guizhou Province of southwest China which was caused by long-term continuous cropping of crops. To reduce the limit factors of continuous cropping of corps has become an urgent problem. Methods Reductive soil disinfestation (RSD) is an environmentally friendly soil amendment technology. In this study, high-throughput sequencing was used to investigate the mechanisms of RSD technology to improve long-term continuous cropping soil health. The examination focused on discerning how RSD influences the composition and structure of the rhizosphere microbial community. Result The results demonstrated that: (1) RSD treatment increased the content of soil organic matter (SOM), alkaline hydrolyzed nitrogen (AN), available phosphorus (AP), available potassium (AK) and pH; (2) RSD changed the fungal and bacterial community structure and the relative abundance of pathogenic microorganisms (e.g., Fusarium) was reduced, while the beneficial microorganisms (e.g., Trichoderma and Penicillium) was increased. (3) AN and pH had a greater impact on the bacterial community in the rhizosphere soil than on the fungal community. (4) RSD treatment improved the agronomic traits of tobacco and reduced the disease incidence of root rot disease. Conclusion Our results revealed that RSD treatment improved the physicochemical properties of continuous cropping tobacco soil and maintain the soil nutrient balance, resulting in the effective alleviation of continuous cropping barriers.